2018
DOI: 10.1016/j.jcin.2017.10.014
|View full text |Cite
|
Sign up to set email alerts
|

Early Outcomes With the Evolut PRO Repositionable Self-Expanding Transcatheter Aortic Valve With Pericardial Wrap

Abstract: The safety and efficacy results of this study support the use of the Evolut PRO System for the treatment of severe symptomatic aortic stenosis in patients who are at increased surgical risk, resulting in excellent hemodynamics and minimal paravalvular leak (The Medtronic TAVR 2.0 US Clinical Study; NCT02738853).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

17
72
4

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 159 publications
(93 citation statements)
references
References 26 publications
17
72
4
Order By: Relevance
“…The improvement in device success was driven by a significant reduction in moderate paravalvular regurgitation (1.7%). These findings are in keeping with the low incidence of moderate paravalvular regurgitation (0.0%) reported in the Evolut PRO US clinical study …”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…The improvement in device success was driven by a significant reduction in moderate paravalvular regurgitation (1.7%). These findings are in keeping with the low incidence of moderate paravalvular regurgitation (0.0%) reported in the Evolut PRO US clinical study …”
Section: Discussionsupporting
confidence: 89%
“…The outer pericardial wrap could also potentially lead to an increase in conduction disturbance. However, we demonstrated a similar incidence of new permanent pacemaker implantation (17.8% of patients without a pacemaker at baseline) to previous studies of self‐expanding prostheses (11.8–19.7%) . Preexisting right bundle branch block was identified as a strong risk factor for new permanent pacemaker (57.1%), as has been previously been described .…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…These findings represent a definite improvement on the outcomes seen with the first‐generation CoreValve in the ADVANCE clinical study (15.0%) . However, incidence of more than mild paravalvular regurgitation was not as low as has been recently reported in the Evolut R FORWARD clinical study (1.9%), Evolut R 34 mm U.S. clinical study (1.7%), Evolut PRO U.S. clinical study (0.0%) and other 34 mm Evolut R registry data (0.0%–5.0%) . The average implant depth in our study (5.6 ± 3.1 mm) was outside the manufacturer recommendations (3–5 mm), which may explain the higher incidence of more than mild paravalvular regurgitation that we have reported.…”
Section: Discussionmentioning
confidence: 53%
“…In addition, 4 THVs, Evolut PRO, Edwards Centera, SAPIEN 3 Ultra and Myval, received CE mark approval in 2017, 2018, 2018 and 2019 respectively. Clinical endpoints are reviewed in a few articles [11][12][13] and studies showed 30-day mortality rates of 1.7% (Evolut PRO [14,15]) and 1% (Centera [14,15]) and 9.1% 1-year mortality rate for Centera [11][12][13][14][15]. Articles describing clinical endpoints of Myval were not identified.…”
Section: Transcatheter Heart Valvesmentioning
confidence: 99%